The Condition Mangrove Forests In Coastal Area Tanjung Balai Karimun Karimun Regency Kepulauan Riau Province - Yanti, Novi; ', Zulkifli; ', Thamrin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conductes in April 2016 in Coastal Area Tanjung BalaiKarimun. The purpose of this study is to find a community structure mangrove andunderstanding of the conditions mangrove forests in Coastal Area Tanjung BalaiKarimun. The method used in this research is survey method, with counting diametermangrove, distinguish tree, saplings, counting density according to structuremangrove, and identify the types of mangrove at the station. The result showed thatmangrove condition of the station is damaged. A kind of vegetation mangrove thatwere found in Coastal Area consisting of a kind of Sonneratia alba, Sonneratiacaseolaris, Avicennia lanata, and Rhizophora lamarckii. Index value important at agroup of trees the highest which is a kind of A. lanata 107,13% (station 1), in station2 IVI highest kind of S. alba 229,08%, and IVI on the highest station 3 that is a kindof S. alba 138,35%. To the highest IVI saplings station 1 has on the type of R.lamarckii 163,68%, in station 2 IVI highest kind of S. alba 191,43%, and IVI on thehighest station 3 that is a kind of S. caseolaris 200,97%.Keywords: Mangrove, Density, Index Value Important